Construction of sidewalk - Sadali, Muhammad Afif (Universiti Teknologi MARA, Perak, 2021)
Wall is one of main element in a building. Wall is an element to create partition inside and outside the building. There are several type of wall such as load bearing wall, cavity wall, partition wall, etc, each type of wall have different role and importance to a building and the process also have different step and method. Therefore, this report discussed on construction of wall for single storey bungalow for Encik Faizal located on Kampung Bintang, Peserai, Batu Pahat, Johor. The objective of this report is to identify method construction of wall and tool and machineries that used in this project. This study is conducted by using three appropriate method such as observation, interview and referring online resources. As the result, to construct a wall, the first method is setting out because a new project on empty land. After that, excavate foundation, installing reinforcement, install formwork for foundation and concrete work. After that, beam and column should be construct before staring brickwork process. Then, proceed to plastering work and finishing of the wall. There are also several tools and machineries that used in this project such as excavator, concrete mixer, water balance, trowel tools, bucket, and paint roller.